Image quality and entrance surface dose evaluation for lateral cervical spine: a study using grid and non-grid techniques - Moey, Soo Foon; Mohd Ramlee, Nurfatin Nabilah (Iranian Association of Medical Physicists (IAMP), 2018)
Introduction: The purpose of this study is to ascertain the effect of a moving grid, stationary grid and non-grid in the lateral cervical spine radiography on image quality and entrance surface dose (ESD). Image quality and radiation doses have been studied by various authors, but there is limited amount of information available on image quality and patient dose from cervical spine examination with different grid techniques. Materials and Methods: The radiographs of the lateral cervical spine were acquired by positioning the RANDO phantom abutting the erect bucky whilst using a moving grid, stationary grid and non-grid. A 24 cm x 30 cm Fuji standard cassette type imaging plate was used in this study. A Leeds TOR test tool was utilized for relative comparison of image quality for the fore mentioned techniques. The ESD of each examination was determined by using the Optically Stimulated Luminescence Dosimeter (OSLD). Results: Increased kilovoltage (kVp) resulted in the reduction of ESD whether moving grid, stationary grid or non-grid was utilized. Significant differences in high contrast sensitivity, low contrast sensitivity and spatial resolution were reflected when using the grid compared to that of non-grid, x2(2, N=42) = 8.000; 5.000, p<0.05. The results also indicated significant differences in ESD when using a moving grid, stationary grid and non-grid, x2(2, N=42) = 7.200, p<0.05. Conclusion: This study reflected that there were significant differences in image quality and ESD when a moving grid, stationary grid and non-grid were used in lateral cervical spine radiography. Further, non-grid cervical spine lateral radiography using the highest appropriate kVp is recommended as the existed air gap acts as a grid, resulting in acceptable image quality with reduction in ESD.